ANALISA BREAK EVENT POINT (BEP) TERHADAP LABA PERUSAHAAN - Ferisanti, Ferisanti; Dwita, Febrisi; Supardi, Supardi; Mislawardah, Mislawardah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Breakeven point or breakeven point is a situation where a company that carries out business activities does not get profit or loss. The purpose of the breakeven point is to provide an overview of the break event and also how it relates to company profits and to provide an overview of the results of the company's business activities. This break event point analysis is very useful for companies to determine the company's production, starting from how much it costs to incur, what price is set so that the company does not experience losses. The break event point will determine the link between prices, costs, sales, production, losses and profits, making it easier for company leaders to make decisions for the company